The effect of thin capitalization and executive character on tax avoidance with institutional ownership as a moderating variable - Nurindah Rizki Dian Gunadi; Yongky Rangga Yuda Nugraha (Akuntansiku, 2026)
This study examines the effect of thin capitalization and executive characteristics on tax avoidance, as well as the moderating role of institutional ownership in mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research adopts a quantitative approach using 151 observations from 43 companies selected through purposive sampling. Data were analyzed using multiple linear regression. The results indicate that thin capitalization has a negative effect on tax avoidance, while executive characteristics have a positive effect. Institutional ownership is proven to weaken the effect of thin capitalization on tax avoidance, but it does not moderate the effect of executive characteristics. These findings suggest that institutional monitoring is more effective in controlling debt-based financing policies than tax-related decisions influenced by executives’ risk preferences.